Determining propulsive force in front crawl swimming - Berger, M. A. M.; Hollander, A. P.; Groot, G. de (Journal of Sports Sciences, 1999)
Propulsive forces during front crawl swimming using arms only were calculated with a three-dimensional kinematic analysis combined with data of lift and drag coefficients obtained in fluid laboratories (Fp-3D). Since for any given constant swimming speed the mean propulsive force should be equal to the mean drag force acting on the body of the swimmer, mean values of Fp-3D were compared with mean drag force (D) obtained from measurements on the MAD-system. The two methods yield comparable values. The mean difference between Fp-3D and D is only 5% (2N). It is concluded that propulsive force values obtained from a three-dimensional kinematic analysis method yield realistic values. The calculation of Fp-3D appears to be rather sensitive to the point on which the hand velocity is quantified and less sensitive to the orientation of the hand.